The role of adipose and muscle tissue breakdown on interorgan energy substrate fluxes in a Pseudomonas aeruginosa induced sepsis model in female pigs - Ryan Morse; Gabriella A. M. Ten Have; John J. Thaden; Marielle P. K. J. Engelen; Sarah Rice; Martin Hagve; Nicolaas E. P. Deutz (Physiological Reports)
Abstract Sepsis leads to an acute breakdown of muscle to support increased caloric and amino acid requirements. Little is known about the role of adipose and muscle tissue breakdown and intestinal metabolism in glucose substrate supply during the acute phase of sepsis. In a translational porcine model of sepsis, we explored the across organ net fluxes of gluconeogenic substrates. In 13 pigs, acute sepsis was induced by IV infusion of Pseudomonas aeruginosa, while in 9 pigs saline (control) was given for 18 h. Blood samples were collected between 12 and 18 h and analyzed with HPLC and LCMS. In sepsis, glucose plasma concentration was reduced (p = 0.0028). A concordant increase in splanchnic area net release of glucose (p = 0.0049), due to reduced uptake in the portal drained viscera (PDV) (p = 0.0032) with an unchanged liver production (p = 0.7861). The hindquarter showed a higher release of alanine (p = 0.0002), glutamine (p = 0.003), and lactate (p = 0.0007), but not for glycerol (p = 0.5718). Diminished PDV uptake of gluconeogenic amino acids, increased liver uptake of these substrates (p < 0.05), while no change in liver glycerol uptake (p = 0.3170), did not lead to an increased net liver glucose release. In the acute phase of sepsis, we hypothesize an important role of altered intestinal amino acid metabolism and breakdown of muscle proteins, but not of glycolysis to support gluconeogenesis.